1994
DOI: 10.1300/j052v13n02_03
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of the "Self-CARE for a Healthy Heart" Program with Older Adults

Abstract: "Self-CARE for a Healthy Heart" promotes healthier dietary practices to reduce cardiovascular disease risk factors. Forty-four adults, aged 60-90, participated. The objectives were to determine if this self-paced program improved dietary habits and to identify how it could be better tailored for elderly. After finishing Self-CARE, 47.8% of respondents reported choosing more low-fat foods. Over 39% reported selecting fewer foods associated with heart disease. Minimal suggestions were made to improve the program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…This would seem to apply particularly to older adults. Mayeda and Anderson (1993) described a print-materials nutrition education program. Their theoretical framework was based on the Health Belief and Stages of Change models, which influenced them to develop print materials that included sections to create reader awareness, interest, practice and reinforcement.…”
Section: Journal Of Nutrition For the Elderlymentioning
confidence: 99%
See 4 more Smart Citations
“…This would seem to apply particularly to older adults. Mayeda and Anderson (1993) described a print-materials nutrition education program. Their theoretical framework was based on the Health Belief and Stages of Change models, which influenced them to develop print materials that included sections to create reader awareness, interest, practice and reinforcement.…”
Section: Journal Of Nutrition For the Elderlymentioning
confidence: 99%
“…Phone interviews revealed that 92% of subjects had read the nutritional tip sheets, 83% reported that they were useful, and 90% reported meeting some or all of their nutritional goals. The authors used self-reported nutrition behavior change without corroborating objective measures, which has been shown to be an unreliable way to determine dietary composition for an elderly population (Arnold et al, 1996;Mayeda and Anderson, 1993). Most of the study outcomes measured showed that the exercise program had significant impact.…”
Section: Nutrition Education For Older Adults 35mentioning
confidence: 99%
See 3 more Smart Citations